Reformulation of Da’wah Communication Paradigm in the Post-Pandemic Era - Ries Dyah Fitriyah; Sokhi Huda; Abd. Mujib Adnan; Tantan Hermansah; Athik Hidayatul Ummah (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2022)
This study focuses on examining the challenges and needs for the reformulation of the da'wah and communication paradigm in the post-pandemic era. Through a qualitative approach, the results of this study show that in the post-pandemic era, da'wah requires a redefinition and reformulation of paradigms, known as the happy da'wah paradigm, namely placing happiness in the experience of the da'wah process and the practice of religious teachings, not on the purpose of da'wah. The performance of the activity system is directed to